Development of a Patient-specific Search of Transplant Program Outcomes and Characteristics: Feedback From Kidney Transplant Patients. Issue 8 (August 2020) - McKinney, Warren T.; Schaffhausen, Cory R.; Bruin, Marilyn J.; Chu, Sauman; Schladt, David; Matas, Arthur; Snyder, Jon; Kasiske, Bertram; Israni, Ajay K.
Abstract : Background: Patients face obstacles in finding a transplant program that meets their healthcare needs. Acceptance criteria and waiting times vary by region and program. The Scientific Registry of Transplant Recipients provides program-specific information, but it is unclear what patients and referring physicians need to know. Methods: We examined variability in program-specific characteristics that could influence access to transplantation. We also conducted 20 interviews and 16 focus groups with transplant candidates, recipients, and their family members. Participants were shown prototypes of a patient-specific search tool and evaluated its capacity to identify programs tailored to the needs of individual patients. Results: The distribution of recipient and donor characteristics that may impact access to transplantation, such as recipients on Medicaid, varied across programs (all with P < 0.01). Several themes emerged related to impressions of access to transplantation and the usability of patient-specific search functions. Perceptions of the prototypes and results varied, but were positive overall and support providing an individualized search of program level data. Participants revealed significant barriers to identifying and evaluating transplant programs and suggest that patient-specific search results reduce the anxiety associated with selecting a program. Conclusions: Providing patient-specific tools is valued by patients and important to maximizing access to transplant.